2013
DOI: 10.3791/50244
|View full text |Cite
|
Sign up to set email alerts
|

New Tools to Expand Regulatory T Cells from HIV-1-infected Individuals

Abstract: CD4+ Regulatory T cells (Tregs) are potent immune modulators and serve an important function in human immune homeostasis. Depletion of Tregs has led to measurable increases in antigen-specific T cell responses in vaccine settings for cancer and infectious pathogens. However, their role in HIV-1 immuno-pathogenesis remains controversial, as they could either serve to suppress deleterious HIV-1-associated immune activation and thus slow HIV-1 disease progression or alternatively suppress HIV-1-specific immunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Regulatory T cells (Tregs) were isolated and expanded as previously described [ 23 , 24 ]. Briefly CD4+ T Cell-enriched PBMC were isolated from peripheral blood of healthy individuals by density centrifugation using the CD4+ T cells RosetteSep enrichment kit (Sigma-Aldrich and STEMCELL Technologies) and labeled with anti-CD3-PE-Cy7, CD4-FITC, CD25-APC and CD127-PE.…”
Section: Methodsmentioning
confidence: 99%
“…Regulatory T cells (Tregs) were isolated and expanded as previously described [ 23 , 24 ]. Briefly CD4+ T Cell-enriched PBMC were isolated from peripheral blood of healthy individuals by density centrifugation using the CD4+ T cells RosetteSep enrichment kit (Sigma-Aldrich and STEMCELL Technologies) and labeled with anti-CD3-PE-Cy7, CD4-FITC, CD25-APC and CD127-PE.…”
Section: Methodsmentioning
confidence: 99%
“…However, the capacity of the HIV-1 to infect these cells impairing its functionality restricts the potential therapeutic use of this strategy in HIV-1-infected subjects. In fact, Angin M et al describes that Treg cells can be isolated from HIV-1-infected subjects and expanded in vitro [ 35 , 36 ], but the capacity of HIV-1 to replicate in these cultured Treg cells compromises the efficacy of these cells and subsequent transfer to the subjects. Here, we clearly demonstrated that the use in vitro of anionic dendrimers could prevent the HIV-1 replication and the infection of expanded Treg cells in culture, which theoretically raises the possibility to use Treg cells therapeutically in HIV-1-infected subjects.…”
Section: Discussionmentioning
confidence: 99%